When Music is Made by AI: Effects on Preferences and Willingness to Pay - Jana Friedrichsen; Julia Schwarz; Michel Clement (Munich Society for the Promotion of Economic Research - CESifo GmbH, 2026)
Artificial intelligence (AI) is rapidly reshaping society, including the music industry. Recent advancements in generative AI enable users to create music from text-based prompts, raising questions about public perception and valuation of AI-generated music. We conducted three studies with German-speaking participants (Study 1: N=2000, Study 2: N=425; Study 3: N=1248) to explore awareness, enjoyment, and willingness to pay for AI music. After finding no clear rejection of AI composed music in Study 1, Study 2 varied whether listeners knew the music was AI-generated. Study 3 involved regular listeners of pop and electronic dance music, manipulating song origin (human vs. AI) and disclosure. Results show that listeners generally could not distinguish between AI and human-made songs. When unaware, participants slightly preferred AI music and valued it equally. However, disclosing that AI had been used to create compositions reduced appreciation and willingness to pay. We explore how reactions differ by genre and individual attitudes toward AI and discuss implications for the music industry and for regulatory initiatives.
Keywords: D12; Z11; O33; 330; artificial intelligence; music; willingness-to-pay; ethics of AI